PENGEMBANGAN MODUL MATA KULIAH ILMU PENGETAHUAN SOSIAL (IPS) PROGRAM STUDI PGSD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN TAHUN AKADEMIK 2014/2015 DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Dodik Eko Yulianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
Module Development Course for Students of Social Education Studies Program PGSD the Faculty of Education Academic Year 2014/2015 in the fourth semester at the University of Abdurachman Saleh Situbondo. explained that the teaching materials used at the University currently drafting often without considering the structure of the content areas of study for learning purposes. Currently ability mastery of Social Education course is still low, so it required the development of teaching materials Education IPS in accordance with the existing field conditions and pay attention to the character of students.Stages of development of teaching materials package for the IPS Education PGSD Studies Program Faculty of Teaching and Education Academic Year 2014/2015 at the University Abdurachman Saleh Situbondo is the selection of teaching materials, media selection, evaluation procedures and product design development. The evaluation was done by an expert course content, instructional media design experts and the PGSD Study Program Student And Teacher Training Faculty of Education Academic Year 2014/2015 at the University Abdurachman Saleh Situbondo. Formative evaluation is done to get feedback from experts and the students to improve teaching materials Education IPS products.Results of the assessment given by expert course content and instructional media design experts on teaching materials product IPS Education Program for Students PGSD the Faculty of Education Academic Year 2014/2015 in the fourth semester at the University of Situbondo Abdurachman Saleh is a very decent, which means that the material IPS Education teaching for the students is very fit for use.Developer concludes Education teaching materials IPS products can be used as a source of learning students in semester IV, as evidenced by the results of the questionnaire and the comments of experts who claim that IPS education teaching materials are very decent. Besides the teaching materials can improve the ability of students by 80% in the procurement of the material that was delivered by the lecturer. Suggestions can be submitted to the developers of teaching materials Education IPS: 1) as a support for the lecturer in lectures Students can help to deliver material on an individual basis according to student ability. 2) Students can increase learning motivation wherever they are